In-situ analysis of the gas- and particle-phase in cigarette smoke by chemical ionization TOF-MS. (April 2017) - Phares, Denis J.; Collier, Sonya; Zheng, Zhongqing; Jung, Heejung S.
Abstract: Mainstream and sidestream smoke samples from two types of cigarette standards (3R4F and 1R5F) were directly analyzed by a chemical ionization mass spectrometer (CIMS). A Walton smoke machine was used to ensure the cigarette is smoked in an acceptably reproducible manner among experiments. Gas-phase material was analyzed in real time and particles were collected on a Nichrome filament, and desorbed at 500° C for analysis immediately after collection was complete. Nicotine was observed to be the most prevalent compound in both phases, indicative of its well-known partitioning behavior. Gas-phase species present in significant amounts in the sidestream samples include benzene, toluene, isoprene, pyridine, 3-ethenylpyridine, xylene, naphthalene, isoquinoline, myosmine, and nicotyrine. Mainstream gas samples exhibited different signatures, dominated by acetaldehyde, acetone, pyrrole, pyrroline, pyrrolidine, and phenolics. These may be indicative of the higher temperature combustion and filtration during each puff. Concentrations of each gas-phase compound were estimated from a mass calibration using toluene vapor. Spectra obtained for the particle-phase contain a complex mixture of high-molecular weight compounds, as previously observed by off-line methods, but also lower molecular weight semi-volatile compounds smaller than nicotine. This gas/particle partitioning may have implications concerning how some of these compounds are absorbed upon inhalation. These compounds are present in the particle-phase and the gas-phase. The soft ionization technique showed a promising result for rapidly identifying chemical differences among cigarette types, smoke streams, and phase. Highlights: Characterization of cigarette smoke using a chemical ionization mass spectrometer. Rapid identification of chemical differences among cigarette types, smoke streams, and phase.